Engineering of Burkholderia thailandensis strain E264 serves as a chassis for expression of complex specialized metabolites - Wang, Zong-Jie; Liu, Xiaotong; Zhou, Haibo; Liu, Yang; Zhong, Lin; Wang, Xue; Tu, Qiang; Huo, Liujie; Yan, Fu; Gu, Lichuan; Müller, Rolf; Zhang, Youming; et al. (Frontiers in Microbiology, 2022)
Heterologous expression is an indispensable approach to exploiting natural products from phylogenetically diverse microbial communities. In this study, we constructed a heterologous expression system based on strain Burkholderia thailandensis E264 by deleting efflux pump genes and screening constitutive strong promoters. The biosynthetic gene cluster (BGC) of disorazol from Sorangium cellulosum So ce12 was expressed successfully with this host, and the yield of its product, disorazol F2, rather than A1, was improved to 38.3 mg/L by promoter substitution and insertion. In addition to the disorazol gene cluster, the BGC of rhizoxin from Burkholderia rhizoxinica was also expressed efficiently, whereas no specific peak was detected when shuangdaolide BGC from Streptomyces sp. B59 was transformed into the host. This system provides another option to explore natural products from different phylogenetic taxa.